THE EFFECTIVENESS OF EDUCATION AND TRAINING PROGRAMS FOR NON-MILITARY PERSONNEL IN THE INDONESIAN NAVAL - Lawahery, Elphido Theopilos; Sulistiyanto, Sulistiyanto; Taufik, Wildan; Sudirman, Sudirman; Umiyati, Sri (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2023)
Non-military personnel are a complement (complementary) of Indonesian Armed Forces soldiers. Therefore, NonMilitary Personnel and Indonesian Armed Forces soldiers are an integrated unit and are responsible for carrying out the main tasks of the Indonesian Armed Forces. This integration must be reflected in all levels of the organization and must understand the roles of each. The use of Non-Military Personnel within the Indonesian Armed Forces environment is carried out based on the consideration that there are needs and demands for specific tasks that are more effective and efficient when held by Indonesian Armed Forces Non-Military Personnel, so as to ensure the continuity of the Indonesian Armed Forces's main tasks. The research objectives to be achieved are to describe and analyze the Effectiveness of the Education and Training Program (Training) in the Regulation of the Indonesian Armed Forces Commander Number 161/XII/2011 concerning the Development of Non-Military Personnel in the Account Office of the Regional Financial Officers Koarmada II as well as describe and analyze factors support and inhibitors. The type of research used is qualitative research. The results of the study show the Effectiveness of the Non-Military Personnel Education and Training Program (Training) for NonMilitary Personnel in the Regulation of the Indonesian Armed Forces Commander Number 161/XII/2011 to Foster Non-Military Personnel Indonesian Armed Forces Navy Personnel (Case Study of Non-Military Personnel in the Financial Management Accounts of the Regional Military Command II) Based on the 5 variables that the author conveys can be it was concluded that the education and training programs were quite effective in improving the performance of Non-Military Personnel both in terms of knowledge, skills and attitudes and behavior of NonMilitary Personnel. The effectiveness of the education and training program (Diklat) on the implementation of education and training to improve the performance of Non-Military Personnel, it can be concluded that with the implementation of education and training many Non-Military Personnel have experienced changes, both changes in behavior and changes in work attitudes. Keywords: Effectiveness, Education, Training Program, Non-Military Personnel, Financial Management Accounts.